Analisis Faktor yang Mempengaruhi Kinerja Biaya dan Kinerja Waktu pada Proyek Konstruksi di Dinas Perumahan, Kawasan Permukiman dan Pertanahan Kota Pagar Alam - Masagus Taswin; Ajeng Behaj Zuchruf (Jurnal Ilmiah BERING, 2023)
Late completion times and increased costs often occur in the recent implementation of construction projects, and Pagar Alam City is no exception. For this reason, further analysis is needed. This study aims to determine what factors affect cost performance and time performance on construction projects at the Department of Housing, Settlement and Land in Pagar Alam City. The analytical method used in this study is a quantitative descriptive analysis method by distributing questionnaires to the respondents, in this case the construction actors. The results of the study indicate that changes in material prices on the market and from suppliers from the previous period are factors that greatly influence cost performance, while the number of workers and the volume of work are factors that greatly affect time performance.